PENERAPAN PERATURAN MAHKAMAH AGUNG NOMOR 4 TAHUN 2019 DALAM MENYELESAIKAN GUGATAN SEDERHANA DI PENGADILAN NEGERI PADANG - Dini Azani; Firdaus Firdaus; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Supreme Court issued Supreme Court Regulation Number 4 of 2019 to assist parties who resolve their cases with simple claims settlement in the Court , Article 13 explains the attendance of the parties at the trial. The Padang District Court is a court that has implemented Supreme Court Regulation Number 4 of 2019 in Resolving a Simple Lawsuit at the Padang District Court. The problem in this thesis discusses the first, How is the Application of Supreme Court Regulation Number 4 of 2019 in resolving simple claims at the Padang District Court? And secondly, what are the legal consequences of implementing Supreme Court regulation Number 4 of 2019 in resolving a simple lawsuit at the Padang District Court if one of the parties is not present in court?This type of research can be classified in the type of sociological research, because the author directly conducts research on the location or point being examined to provide a complete and clear picture of the problem being examined. This research was conducted at the Padang District Court, while the sample population was all parties related to the problems studied in this study, the data sources used, primary data and secondary data, data collection techniques in this study were literature review interviews and data analysis.The conclusion of the author regarding the application of the Supreme Court Regulation Number 4 of 2019 in resolving a simple lawsuit at the Padang District Court. 2019 in resolving a simple lawsuit at the Padang District Court if one of the parties is not present at the trial is the party who has objections to the judge's decision can file an objection by registering the case again with the Court so that it can be registered with a new case number, but the plaintiff must carry out the decision which the judge imposes on the case first. As well as the need to increase socialization to the public regarding the settlement of cases with simple lawsuits, so that the parties can overcome losses.Keywords: Plaintiff, Defendant and Simple Claim